Conflict Coaching for Organizational Effectiveness in an Era of Chaos - Alli, Julie (Applied Dispute Resolution Journal, 2023)
Conflict coaching is a one-to-one communication process by which an individual learns and develops their conflict-related understanding, as well as interaction strategies and skills, with the professional help of a conflict coach. Conflict coaching co-actively helps individuals identify and destroy barriers that prevent negotiation and conflict resolution. Assuring individuals that they are creative, resourceful, and whole when it comes to making their own discoveries and high-quality decisions in life empowers them to resolve current and future conflicts in any area of their life. Conflict cannot always be resolved, and with the support of a conflict coach, individuals can learn how to manage conflict.